2014
DOI: 10.1051/0004-6361/201423447
|View full text |Cite
|
Sign up to set email alerts
|

Observational properties of low-redshift pair instability supernovae

Abstract: Context. So-called superluminous supernovae have been recently discovered in the local Universe. It appears possible that some of them originate in stellar explosions induced by the pair instability mechanism. Recent stellar evolution models also predict pair instability supernovae from very massive stars at fairly high metallicities (i.e., Z ∼ 0.004). Aims. We provide supernova models and synthetic light curves for two progenitor models, a 150 M red supergiant and a 250 M yellow supergiant at a metallicity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 96 publications
(134 reference statements)
7
76
0
Order By: Relevance
“…A&A 581, A15 (2015) supernovae (Quimby et al 2011;Lunnan et al 2013) occur preferentially in low-metallicity dwarf galaxies. This may corroborate the idea that reduced wind mass-loss at low metallicity (Vink et al 2001;Mokiem et al 2007) may allow for rapid rotation rates (Yoon et al 2006;Georgy et al 2009) and very massive Yusof et al 2013;Kozyreva et al 2014) supernova progenitors. A good understanding of the evolution of metal-poor massive stars is, therefore, important to probe the origin of these extremely energetic explosions.…”
Section: Introductionsupporting
confidence: 74%
“…A&A 581, A15 (2015) supernovae (Quimby et al 2011;Lunnan et al 2013) occur preferentially in low-metallicity dwarf galaxies. This may corroborate the idea that reduced wind mass-loss at low metallicity (Vink et al 2001;Mokiem et al 2007) may allow for rapid rotation rates (Yoon et al 2006;Georgy et al 2009) and very massive Yusof et al 2013;Kozyreva et al 2014) supernova progenitors. A good understanding of the evolution of metal-poor massive stars is, therefore, important to probe the origin of these extremely energetic explosions.…”
Section: Introductionsupporting
confidence: 74%
“…This is because its light-curve (LC) decline rate after the LC peak is consistent with the nuclear decay rate of 56 Co and strong nebular Fe emission lines are also observed, as expected in PISNe (e.g., Kasen et al 2011;Dessart et al 2013;Kozyreva et al 2014;Whalen et al 2014;Chatzopoulos et al 2015).…”
supporting
confidence: 72%
“…7 are too short to correspond to PISNe (Kasen et al 2011;Dessart et al 2013;Kozyreva et al 2014;Chatzopoulos et al 2015 but see also Kozyreva et al 2016). On the contrary, many slowlydeclining SLSNe have decline rates which are surprisingly similar to that of the 56 Co decay as discussed in Section 1.…”
Section: Magnetar Vsmentioning
confidence: 99%
“…Much work has been dedicated to modelling the appearance of PISNe during the shock breakout and diffusion phases (Kasen, Woosley & Heger 2011;Dessart et al 2012;Whalen et al 2013a;Dessart et al 2013;Chatzopoulos, Wheeler & Couch 2013;Whalen et al 2014;Smidt et al 2015;Chatzopoulos et al 2015;Kozyreva & Blinnikov 2015), and fitting of these models to observed candidates. The ability of central engine (magnetar spin-down or accreting black hole, Kasen & Bildsten 2010;Woosley 2010;Dexter & Kasen 2013) and circumstellar interaction (Smith et al 2007;Chevalier & Irwin 2011;Ginzburg & Balberg 2012) models to produce similar light curves has, however, left interpretation of observed long-duration events ambiguous Nicholl et al 2013;Moriya et al 2013;McCrum et al 2014).…”
Section: Introductionmentioning
confidence: 99%